2014
DOI: 10.5516/net.03.2014.701
|View full text |Cite
|
Sign up to set email alerts
|

Treating Uncertainties in a Nuclear Seismic Probabilistic Risk Assessment by Means of the Dempster-Shafer Theory of Evidence

Abstract: International audienceThe analyses carried out within the Seismic Probabilistic Risk Assessments (SPRAs) of Nuclear Power Plants (NPPs) areaffected by significant aleatory and epistemic uncertainties. These uncertainties have to be represented and quantifiedcoherently with the data, information and knowledge available, to provide reasonable assurance that related decisions can betaken robustly and with confidence. The amount of data, information and knowledge available for seismic risk assessment istypically l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For example, a flooding analysis may use a computation fluid dynamics (CFD) or a finite element (FE) model [4,17,18,19]. Multiple simulation-based fragility curves can be generated by including epistemic uncertainty for the simulation median capacity (or median of the simulated lognormal fragility function) as shown in Figure 2 (a) [20,21]. In the performance-based risk-informed validation framework, binary trees (fault and event trees) are mapped into a Bayesian network using a mapping algorithm [22].…”
Section: Performance-based Risk Informed Validation Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a flooding analysis may use a computation fluid dynamics (CFD) or a finite element (FE) model [4,17,18,19]. Multiple simulation-based fragility curves can be generated by including epistemic uncertainty for the simulation median capacity (or median of the simulated lognormal fragility function) as shown in Figure 2 (a) [20,21]. In the performance-based risk-informed validation framework, binary trees (fault and event trees) are mapped into a Bayesian network using a mapping algorithm [22].…”
Section: Performance-based Risk Informed Validation Frameworkmentioning
confidence: 99%
“…Multiple simulation fragility curves are generated by assuming a coefficient of variation of 0.1 for the simulation median capacity. Similarly, multiple data-driven fragility curves are generated by including data applicability [2,20,21].…”
Section: Safe-binary/cliff-edge Conditionmentioning
confidence: 99%
“…Structural analysis methods are further discussed in Section 2.3. Uncertainty can also be modeled using probabilistic methods such as Bayesian statistics [26,27], which combines experts' judgment and scarce data, or non-probabilistic methods such as the Dempster-Shafer theory [28] of evidence or fuzzy sets [29]. The choice is mostly driven by the availability of data, hence when sufficient data are available, as assumed to be the case in PSDA, statistical methods based on numerical models or data are more favorable [30].…”
Section: Treatment Of Uncertainty In Pbeementioning
confidence: 99%
“…For example, in Cruz et al (2009), a worst case analysis of tsunamis impacting an oil refinery is reported. In Prasad (2012) and Lo (2014), applications to a nuclear power plant are described. However, these approaches have proven to be limited in modelling seismic sources as well as tsunamis due to the large uncertainty given by the scarcity of tsunami observations (Geist & Parsons, 2014).…”
Section: Acronymsmentioning
confidence: 99%